A comparative analysis of science and technology policies of three countries and its relevance to Lesotho - Williams, Maseqobela Bernadette (Stellenbosch : University of Stellenbosch, 2008)
Thesis (M.Phil (Science and Technology Studies))--University of Stellenbosch, 2005.